2012
DOI: 10.1093/scan/nss028
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal correlates of social cognition in borderline personality disorder

Abstract: Patients with borderline personality disorder (BPD) have severe problems in social interactions that might be caused by deficits in social cognition. Since the findings about social-cognitive abilities in BPD are inhomogeneous, ranging from deficits to superior abilities, we aimed to investigate the neuronal basis of social cognition in BPD. We applied a paradigm with three social cognition tasks, differing in their complexity: basal processing of faces with a neutral expression, recognition of emotions, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 61 publications
8
86
2
4
Order By: Relevance
“…However, while the control participants showed increasing activation in areas of the social brain with increasing complexity in the social-cognitive task, BPD patients had hypoactivation in these areas and hyperactivation in the amygdala, effects that were not modulated by task complexity. From this activation pattern, the authors concluded that there is an enhanced emotional approach in the processing of social stimuli in BPD that allows good performance in standardised social-cognitive tasks, but might be the basis of social-cognitive deficits in real-life social interactions (Mier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, while the control participants showed increasing activation in areas of the social brain with increasing complexity in the social-cognitive task, BPD patients had hypoactivation in these areas and hyperactivation in the amygdala, effects that were not modulated by task complexity. From this activation pattern, the authors concluded that there is an enhanced emotional approach in the processing of social stimuli in BPD that allows good performance in standardised social-cognitive tasks, but might be the basis of social-cognitive deficits in real-life social interactions (Mier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Human social cognition refers to the ability to accurately perceive and process conscious and unconscious social signals [48]. Functional impairment in interpersonal relationships in individuals with BPD may be related to fundamental deficits in processing social information [49]. Much of the research on social cognition in BPD has focused on two aspects: impaired theory of mind (ToM) and altered emotion sensitivity and recognition.…”
Section: Disturbed Interpersonal Relationshipsmentioning
confidence: 99%
“…Positing that ToM could be sub-divided into multiple components, Mier et al [49] administered a task to a sample of individuals with BPD and HCs to assess different aspects of ToM: 1) neutral face processing, 2) emotion recognition, and 3) understanding emotional intent. In this task, participants were shown a statement about an emotional intention, an emotional state, or a physical feature of a depicted person [65].…”
Section: Neural Network Tom and Bpdmentioning
confidence: 99%
See 1 more Smart Citation
“…Key findings include reduced activity in the left superior temporal cortex when inferring others' mental states together with increased responsiveness of the right midinsula and left posterior insula when sharing others' emotions (Dziobek et al, 2011;Mier et al, 2013;Roepke et al, 2013). In addition, activity in the temporoparietal junction and superior temporal sulcus scaled negatively with borderline symptoms in an emotional perspective-taking task (Haas and Miller, 2015).…”
Section: Introductionmentioning
confidence: 98%